THE PROBLEM OF TEXTBOOKS AS A COMPONENT OF THE FORMATION OF NATURAL EDUCATION - Yana Prystupa (Scientific Journal of Polonia University, 2022)
The modern educational system requires the teacher to form in students certain competencies, choosing a logically structured didactic material. School textbooks play an important role in building competency-based learning. They can actualize students' subjective problems, turn them into cognitive ones, and teach them how to solve them. The analysis of textbooks gives grounds to conclude that the authors, developing textbooks, followed the path of partially adapting them to modern conditions and tasks. The key features of the textbook's compliance with the formation of individual characteristics of students in the modern educational paradigm are identified, namely: saturation of terminology, headings, saturation of tables and graphs, support for Internet resources. In the process of analyzing the existing textbooks, we also identified the following shortcomings: terms that are too difficult to understand and not logical construction of the material.